2022
DOI: 10.3390/su15010294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Portuguese Public Hospitals Performance: Any Difference before and during COVID-19?

Abstract: COVID-19 is a well-known respiratory disease that has spread worldwide since January 2020, causing many deaths and massive pressure on health systems. This pandemic’s appearance compromised health service sustainability and quality as many procedures were postponed or canceled, with an expected increase of adverse events like nosocomial infections, in-hospital deaths, and the worsening of the patient’s clinical status. For instance, the year 2020 featured an increase in undesirable results in Portugal: a rise … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…This result suggests that changes in performance should be interpreted in the light of internal structure (poor preparedness, staff burnout, hysteria, among others). As the World Health Organization has already decreed the pandemic's end, it is important that healthcare providers and governments prepare themselves for likely future pandemics, by following the best practices (benchmarks) and designing reliable contingency plans [104][105][106].…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that changes in performance should be interpreted in the light of internal structure (poor preparedness, staff burnout, hysteria, among others). As the World Health Organization has already decreed the pandemic's end, it is important that healthcare providers and governments prepare themselves for likely future pandemics, by following the best practices (benchmarks) and designing reliable contingency plans [104][105][106].…”
Section: Discussionmentioning
confidence: 99%
“…The development of information systems to increase efficiency; -Reducing copayments to promote equity in terms of access; -Expanding primary healthcare to increase the scope of the services provided in primary care centres (exams, oral health appointments, visual health screenings); -Establishing incentives, either financial or not, to increase the social mobility of doctors from deprived areas and increase efficiency and equity in terms of access; -Sharing resources between SNS hospitals to increase efficiency and equity in terms of access [3,6,15].…”
Section: The Evolution Of Health Reforms In Portugalmentioning
confidence: 99%
“…Moreover, the advent of the COVID-19 pandemic exacerbated the preexisting issue of limited access to healthcare services. Additionally, the introduction of transparency measures such as the publication of data and information pertaining to care provision revealed certain inefficiencies that have contributed to user discontentment [15].…”
Section: The Inefficiencies Of the Snsmentioning
confidence: 99%
“…[12] Some studies have analyze the organizational performance before and during COVID-19 in companies, [13][14][15] banks, [16][17][18] and libraries, [19] and very few studies have focused on the performance of medical institutions. [20,21] For example, Nunes and Ferreira [21] concluded that the efficiency of public hospitals dropped when COVID-19 started, and then recovered to prepandemic levels because of the actions taken by the Portuguese state. Caldas and Varela [22] also confirmed a drop in Portuguese public hospitals' performance during COVID-19.…”
Section: Introductionmentioning
confidence: 99%